IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGS), GOAL 8 PADA PELAKU USAHA MIKRO DI DESA PADAS, KECAMATAN KARANGNOM DAN DESA BONYOKAN, KECAMATAN JATINOM, KABUPATEN KLATEN - Rahmat Handoyo; Sofie Sofie; Nurhastuty Wardhani (Jurnal Akuntansi Trisakti, 2023)
The Sustainable Development Goals (SDGs) is a global development agenda which contains 17 goals and is divided into 169 targets with a period of achievement of up to 2030. This study aims to determine the real impact of implementing the 8 SDGs goals in Padas Village and Bonyokan Village by knowing the level of the understanding of micro business actors is the same as that of village and private stakeholders in realizing the targets on the criteria for goal 8 SDGs. In this study, researchers based on institutional theory with a qualitative and exploratory research method that used the 17 criteria of SDGsgoal 8 as a research basis. The unit of analysis is micro business actors, village stakeholders and private stakeholders. The results of the research show that SDGs Goal 8 has not been socialized effectively, both village stakeholders, micro business actors and private stakeholders. This can be seen from the low understanding of the respondents on the variables and sub-indicators of SDGs Goal 8. The implication of this research is the need to re-socialize the definitions and indicators of each SDGs to local governments, private stakeholders and the general public in order to realize the Goals SDGs by 2030.